Procrastination, perceived maternal psychological control, and structure in math class: The intervening role of academic self‐concept - Selçuk, Şule; Koçak, Aylin; Mouratidis, Athanasios; Michou, Aikaterini; Sayıl, Melike (Wiley, 2021)
AbstractDo students procrastinate less when their parents psychologically press them to study? Or do they show procrastination when classroom environment lacks structure? In this study, we aimed to investigate to what extent perceived maternal psychological control and perceived classroom structure in math class relate to adolescents' academic procrastination in math via adolescents’ academic self‐concept in math. Three hundred fifty‐three adolescents (M age = 16.86 years, SD = 1.35) rated maternal psychological control, structure provided by their math teachers, their own academic self‐concept in math, and academic procrastination in math. Results from structural equation model indicated that procrastination in math was positively predicted by achievement‐oriented psychological control and negatively by perceived provision of structure by means of academic self‐concept in math. Based on the current findings, we provided some suggestions for school counselors and other specialists.
Keywords: Achievement‐oriented psychological control; Concept; Academic self‐; Academic procrastination; Dependency‐oriented psychological control; Perceived structure; Oriented psychological control; Achievement‐; Academic self‐concept; Dependency‐; 4. Education